Premature sexual initiation - a problem or an everyday occurrence for today's adolescents - Pawłowski, Piotr; Szymańska, Kamila; Nowak, Katarzyna; Kościołek, Aneta (Quality in Sport, 2024)
Human sexuality is a component of a holistic being, a biopsychosocial state, defined by the World Health Organization as health. It is manifested in aspects of relationship, desire, sexual behavior, orientation, among others. Every year, more and more reports say that the age of sexual initiation is shifting towards younger years. It is worth noting that, according to analyses, the sexuality of the young does not differ from that of the 20th century. In boys, the motivation to engage in sexual activity is usually lust, in girls it is love and emotion. This condition is influenced by many factors: biological, genetic, environmental, family, as well as psychological factors like personality and temperament. The health care system should promote appropriate sexual behavior, along with sex education and awareness of the consequences of risky behavior, including those related to venereal aspects.